Effect of Diesel-Ethanol Blends as Fuels on Performance and Emissions of a Diesel Truck Engine - Nguyen, Van Nhinh; Pham, Minh Tuan; Pham, Huu Tuyen (Old Journal, 2018)
Recently, the alternative fuels have been widely researched and applied on internal combustion engine in many countries in all over the world because of fossil fuels limit and strict emission regulations. Among biofuels, ethanol is one of the most potential alternative fuels that is normally used for spark ignition engines and also possible for diesel engines. This paper presents an experimental research on performance and emissions of Hyundai D4BB 1.25 ton diesel engine truck using diesel-ethanol blends with different ratio of ethanol which are ED5 (95% diesel and 5% ethanol by voumel) and ED10 (90% diesel and 10% ethanol by volume) at full load. The results showed that there was a minor change in engine torque and fuel consumption, while HC and CO emissions and smoke reduced quite clearly, but NOx emissions increased a bit when using ethanol-diesel blends as compared to conventional diesel.